1981
DOI: 10.1002/macp.1981.021820245
|View full text |Cite
|
Sign up to set email alerts
|

Functional monomers and polymers, 91. On the adsorption of iodine and bromine onto polystyrene‐grafted chitosan

Abstract: Chitosan is a polysaccharide consisting predominantly of unbranched chains of /l-( 1,4)-2-. amino-2-deoxy-D-glucose residues. It can be readily obtained by hydrolysis from chitin, which exists naturally in fungi and arthropods. Recently, the effective use of chitin and chitosan'), and their congeners2-4, for inorganic chromatography has been demonstrated, as they can act as excellent chelating agents. It was also found that the adsorption ability of chitosan is generally much higher than that of chitin. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Polystyrenegrafted chitosan films showed less swelling and better elongation in water than chitosan films. 21,22 Chitosan grafted with poly(acrylic acid) produced a hydrogel with enhanced water uptake. 23 Chitosan and its derivatives are becoming increasingly important because of their metal chelating ability.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrenegrafted chitosan films showed less swelling and better elongation in water than chitosan films. 21,22 Chitosan grafted with poly(acrylic acid) produced a hydrogel with enhanced water uptake. 23 Chitosan and its derivatives are becoming increasingly important because of their metal chelating ability.…”
Section: Introductionmentioning
confidence: 99%
“…Some synthetic studies of chitinous graft copolymer have been reported so far. [6] Syntheses of chitin-graft-polystyrene, [8] chitin-graft-poly(methyl methacrylate), [9] chitin-graftpoly(c-methyl l-glutamate), [10] chitin-graft-poly(2-alkyl-2-oxazoline), [11] and chitin-graft-[poly(2-methyl-2-oxazoFull Paper: A chitin-based graft copolymer, chitin-graftoligo(e-caprolactone) (2), was synthesized via ring-opening graft polymerization of (e-caprolactone (e-CL) to ca. 50% partially deacetylated chitin 1 catalyzed by tin(II) 2-ethylhexanoate in the presence of water as a swelling agent.…”
Section: Introductionmentioning
confidence: 99%
“…line)-block-poly(2-phenyl-2-oxazoline)] [12] have appeared in the literature. As for chitosan derivatives, copolymers with polystyrene, [8] poly(acrylonitrile), [13] poly(vinyl acetate), [13] and poly(vinyl alcohol) [13] have been prepared. Polyesters such as poly(3-hydroxyalkanoate) [14] and poly(d,l-lactic acid) [15] have been introduced to chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…Its biomedical uses, such as wound-heal-HEMA using the gamma irradiation method, ing accelerator, artificial kidney membrane, in have been reported in the literature. 9,10 drug delivery systems, absorbable sutures, and as This article presents the grafting of chitoan antihypocholestermeric agent, are of special san with N,N-dimethylaminoethylmethacrylate interest.…”
Section: Introductionmentioning
confidence: 99%